Characterization of canine tumor-infiltrating leukocyte transcriptomic signatures reveals conserved expression patterns with human osteosarcoma - Dylan T. Ammons; R. Adam Harris; Lyndah Chow; Steven Dow (Cancer Immunology, Immunotherapy)
Abstract Immune cells play key roles in host responses to malignant tumors. The selective pressure that immune cells elicit on tumors promotes immune escape, while tumor-associated modulation of immune cells creates an environment favorable to tumor growth and progression. In this study we used publicly available single-cell RNA sequencing (scRNA-seq) data from the translationally relevant canine osteosarcoma (OS) model to compare tumor-infiltrating immune cells to circulating leukocytes. Through computational analysis we investigated the differences in cell type proportions and how the OS TME impacted infiltrating immune cell transcriptomic profiles relative to circulating leukocytes. Differential abundance analysis revealed increased proportions of follicular helper T cells, regulatory T cells, and mature regulatory dendritic cells (mregDCs) in the OS TME. Differential gene expression analysis identified exhaustion markers (LAG3, HAVCR2, PDCD1) to be upregulated in CD4 and CD8 T cells within the OS TME. Comparisons of B cell gene expression profiles revealed an enrichment of protein processing and endoplasmic reticulum pathways, suggesting infiltrating B cells were activated following tumor infiltration. Gene expression changes within myeloid cells identified increased expression of immune suppressive molecules (CD274, OSM, MSR1) in the OS TME, indicating the TME skews myeloid cells toward an immunosuppressive phenotype. Comparisons to human literature and analysis of human scRNA-seq data revealed conserved transcriptomic responses to tumor infiltration, while also identifying species differences. Overall, the analysis presented here provides new insights into how the OS TME impacts the transcriptional programs of major immune cell populations in dogs and acts as a resource for comparative immuno-oncology research.